Sustained and intermittent hypoxia differentially modulate primary monocyte immunothrombotic responses to IL-1β stimulation - Wahlund, Casper J.E.; Çaglayan, Safak; Czarnewski, Paulo; Hansen, John-Bjarne; Snir, Omri (Frontiers in Immunology, 2023)
Venous thromboembolism (VTE) is a leading cause of preventable deaths in hospitals, and its incidence is not decreasing despite extensive efforts in clinical and laboratory research. Venous thrombi are primarily formed in the valve pockets of deep veins, where activated monocytes play a crucial role in bridging innate immune activation and hemostatic pathways through the production of inflammatory cytokines, chemokines, and tissue factor (TF) – a principal initiator of coagulation. In the valve pocket inflammation and hypoxia (sustained/intermittent) coexist, however their combined effects on immunothrombotic processes are poorly understood. Inflammation is strongly associated with VTE, while the additional contribution of hypoxia remains largely unexplored. To investigate this, we modelled the intricate conditions of the venous valve pocket using a state-of-the-art hypoxia chamber with software-controlled oxygen cycling. We comprehensively studied the effects of sustained and intermittent hypoxia alone, and in combination with VTE-associated inflammatory stimuli on primary monocytes. TF expression and activity was measured in monocytes subjected to sustained and intermittent hypoxia alone, or in combination with IL-1β. Monocyte responses were further analyzed in detailed by RNA sequencing and validated by ELISA. Stimulation with IL-1β alone promoted both transcription and activity of TF. Interestingly, the stimulatory effect of IL-1β on TF was attenuated by sustained hypoxia, but not by intermittent hypoxia. Our transcriptome analysis further confirmed that sustained hypoxia limited the pro-inflammatory response induced by IL-1β, and triggered a metabolic shift in monocytes. Intermittent hypoxia alone had a modest effect on monocyte transcript. However, in combination with IL-1β intermittent hypoxia significantly altered the expression of 2207 genes and enhanced the IL-1β-stimulatory effects on several chemokine and interleukin genes (e.g., IL-19, IL-24, IL-32, MIF), as well as genes involved in coagulation (thrombomodulin) and fibrinolysis (VEGFA, MMP9, MMP14 and PAI-1). Increased production of CCL2, IL-6 and TNF following stimulation with intermittent hypoxia and IL-1β was confirmed by ELISA. Our findings provide valuable insights into how the different hypoxic profiles shape the immunothrombotic response of monocytes and shed new light on the early events in the pathogenesis of venous thrombosis.